Integrasi Kurikulum Pendidikan Islam Dengan Teknologi Digital: Analisis Kesiapan Madrasah Di Era Revolusi Industri 5.0 - Ahmad Taufik; Fatimah Purba; Irhamuddin; Yuslinda; Yusman (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
This study aims to analyze the readiness of madrasahs in integrating digital technology into the Islamic education curriculum in the Industrial Revolution 5.0 era. This integration is important considering the demands of the era that emphasize human and technology collaboration without ignoring Islamic values. The study uses a quantitative explanatory approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Five main variables were studied: infrastructure readiness, teacher digital literacy competency, curriculum limitations, madrasah innovation, and readiness for digital curriculum integration. The results show that infrastructure readiness and teacher competency have a significant effect on readiness for integration. Curriculum limitations are the main obstacle, while madrasah innovation strengthens the positive relationship between variables. This study provides an important empirical picture for policy makers and curriculum developers to design an Islamic education system that is adaptive to digital technology without losing the essence of religious values